Phosphonic group modified nh2-mil-53(fe) material, method of preparation and use thereof
Patent Information
- Application Number
- CN202610834649.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明提出了一种磷酸基团改性NH2-MIL-53(Fe)材料、制备方法及其应用,旨在解决现有技术中存在的质子传导材料在宽湿度范围内性能不足的技术问题
[0017]1、本发明提供的改性NH2-MIL-53(Fe) 是由 FeO6八面体通过反式共角连接形成一维链,链间由混合配体(BDC-NH2和 BDC-PO3H2)桥连,Fe(III)与羧基氧之间的强相互作用导致了所述NH2-MIL-53(Fe)材料的高度稳定性,其优异的结构稳定性为进一步功能化改性以及扩大应用范围奠定了基础。
Smart Images

Figure CN122978458A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fuel cell materials technology, and in particular to a phosphate-modified NH2-MIL-53(Fe) material, its preparation method, and its application. Background Technology
[0002] Currently, commercially used proton exchange membranes are mainly based on perfluorosulfonic acid (Nafion), which exhibits a strength higher than 10 at 60-80℃ and 98%RH. -2 Scm -1 The proton conductivity of Nafion is high. However, its application is limited by its high cost, complex fabrication process, and inability to operate at high temperatures. In recent years, extensive research has been conducted to develop high-performance conductive materials, resulting in the development of various types of conductive materials, including organic polymers and inorganic materials. Among these, metal-organic frameworks (MOFs) are a novel type of proton-conducting material, possessing high crystallinity and tunable structure and properties. Furthermore, MOFs contain high concentrations of acidic groups and water molecules, as well as a continuous hydrogen bond network, providing a carrier and transport channel for protons. However, achieving proton conductivity over a wide humidity range remains a significant obstacle for most MOFs in practical applications. To date, there are very few reports of MOFs achieving proton conductivity over a wide humidity range, mainly because the rigid structure of MOFs disrupts the hydrogen bond network formed by water molecules and acidic groups as the relative humidity (RH) decreases. Therefore, constructing self-adaptive flexible MOFs is crucial for studying their proton conductivity over a wide humidity range.
[0003] NH2-MIL-53(Fe) is one of the few structurally flexible MOF materials, formed by the coordination of FeCl3·6H2O with 2-amino-1,4-phthalic acid (BDC-NH2). NH2-MIL-53(Fe) exhibits excellent structural flexibility, and functional modification of this flexible structure will endow it with good conductivity over a wide temperature and humidity range, which is particularly important for broadening the applicability of proton exchange membrane materials under complex operating conditions. Summary of the Invention
[0004] This invention proposes a phosphate-modified NH2-MIL-53(Fe) material, its preparation method, and its application, aiming to solve the technical problem of insufficient performance of proton-conducting materials in a wide humidity range in the prior art.
[0005] In a first aspect, the present invention provides a phosphate-modified NH2-MIL-53(Fe) material, wherein the modified NH2-MIL-53(Fe) material is obtained by exchanging a portion of the ligand 2-amino-1,4-phthalic acid in NH2-MIL-53(Fe) with 2-phospho-1,4-phthalic acid.
[0006] Furthermore, the NH2-MIL-53(Fe) is formed by the assembly of FeCl3·6H2O and 2-amino-1,4-phthalic acid through coordination.
[0007] Furthermore, in the NH2-MIL-53(Fe), the mass ratio of 2-amino-1,4-phthalic acid to FeCl3·6H2O is 0.5~2.
[0008] Furthermore, the 2-phospho-1,4-phthalic acid is prepared from 2-iodoterephthalic acid via iodination, esterification, phosphorous esterification, and hydrolysis.
[0009] Furthermore, the mass ratio of NH2-MIL-53(Fe) to 2-phospho-1,4-phthalic acid is 1:0.2~0.3.
[0010] Furthermore, the phosphate group doping rate in the modified NH2-MIL-53(Fe) material is 20%~35%.
[0011] Furthermore, the diffraction peaks of the modified NH2-MIL-53(Fe) material in the X-ray powder diffraction pattern are consistent with the theoretically simulated main diffraction peaks of MIL-53(Fe).
[0012] Furthermore, the infrared spectrum of the modified NH2-MIL-53(Fe) material at 1070 cm⁻¹... -1 and 997cm -1 The characteristic absorption peak of the phosphate group is present at the location.
[0013] Secondly, the present invention provides a method for preparing the phosphate-modified NH2-MIL-53(Fe) material as described above, comprising the following steps:
[0014] NH2-MIL-53(Fe) and 2-phospho-1,4-phthalic acid were added to N,N-dimethylformamide and reacted at 120-160℃ for 6-12 h. The reaction product was collected, washed, and dried to obtain the final product.
[0015] Thirdly, the present invention provides an application of the phosphate group-modified NH2-MIL-53(Fe) material as described above in conductive materials.
[0016] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:
[0017] 1. The modified NH2-MIL-53(Fe) provided by the present invention is formed by FeO6 octahedra through anti-cornering connections to form one-dimensional chains, and the chains are bridged by mixed ligands (BDC-NH2 and BDC-PO3H2). The strong interaction between Fe(III) and carboxyl oxygen leads to the high stability of the NH2-MIL-53(Fe) material. Its excellent structural stability lays the foundation for further functional modification and expansion of application range.
[0018] 2. This invention uses 2-phospho-1,4-phthalic acid to modify NH2-MIL-53(Fe), wherein both BDC-PO3H2 and BDC-NH2 contain terephthalic acid, differing only in the substituents at the ortho positions. Through ligand exchange, BDC-PO3H2 partially replaces BDC-NH2, thereby forming a conjugate acid-base pair between the -PO3H2 and -NH2 groups. The acidity of BDC-NH2 is related to the -NH3 group. + The acidic -PO3H2 group of BDC-PO3H2 can provide a proton, and in addition, -PO3H - Group, NH3 + The intermolecular hydrogen bonding between the functional groups and H2O molecules creates a denser proton transport channel, thus providing diverse pathways for proton transfer. After modification with BDC-PO3H2, the modified NH2-MIL-53(Fe) material exhibits increased proton source dissociation capability and shorter proton transition site distances compared to the NH2-MIL-53(Fe) surface, directly resulting in higher proton conductivity.
[0019] 3. The modified NH2-MIL-53(Fe) material provided by this invention has excellent proton conductivity over a wide operating temperature and humidity range. Moreover, it maintains a very high conductivity value under high temperature and high relative humidity conditions, and its proton conductivity hardly decreases after 10 hours of continuous testing. Therefore, it can be widely used as a potential proton conductor in electrochemical devices, sensors, and fuel cells. Attached Figure Description
[0020] Figure 1 The X-ray powder diffraction patterns are those of NH2-MIL-53(Fe) and modified NH2-MIL-53(Fe) prepared in Example 1 of this invention.
[0021] Figure 2 These are the infrared spectra of NH2-MIL-53(Fe) and modified NH2-MIL-53(Fe) prepared in Example 1 of this invention.
[0022] Figure 3 The impedance spectrum of the modified NH2-MIL-53(Fe) material prepared in Example 1 of this invention is shown at 298~343K and 100%RH.
[0023] Figure 4 The impedance spectrum of the modified NH2-MIL-53(Fe) material prepared in Example 1 of this invention is shown at 55%~100% RH and 298K.
[0024] Figure 5 The impedance spectra of the modified NH2-MIL-53(Fe) material prepared in Example 1 of this invention are obtained at 298K and 100% RH and at different times (0~10 h).
[0025] Figure 6 The image shows the Arrhenius spectrum of the modified NH2-MIL-53(Fe) material prepared in Example 1 of this invention at 100% RH and 298~343K. Detailed Implementation
[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] Example 1
[0028] (1) Preparation of NH2-MIL-53(Fe):
[0029] 5 g of BDC-NH2, 8 g of FeCl3·6H2O, and 80 mL of DMF were placed in a stainless steel high-pressure reactor lined with polytetrafluoroethylene and reacted at 160°C for 4 h. The resulting solid was separated by centrifugation, washed with ethanol, and stirred in fresh ethanol for 24 h to remove residual DMF. After solvent exchange, the product was collected and dried under vacuum at 60°C for 24 h to obtain NH2-MIL-53(Fe).
[0030] (2) Preparation of BDC-PO3H2:
[0031] 12 g of 2-iodoterephthalic acid, 60 mL of ice water, and 12.5 mL of concentrated sulfuric acid were mixed thoroughly. Then, 4.65 g of NaNO₂ and 8 g of KI were added, and the mixture was reacted at 100°C for 2 h. The product was filtered and recrystallized from toluene to obtain deep yellow crystals, which is dimethyl 2-iodoterephthalate.
[0032] Subsequently, 2 g of dimethyl 2-iodoterephthalate, 8 mL of trimethyl phosphite, and 0.4 g of PdCl2 were reacted at 120 °C for 4 h under N2 protection. The mixture was cooled and filtered, and the filtrate was stirred in 6 M HCl (60 mL) at 80 °C for 10 h. The mixture was then concentrated under reduced pressure, and the concentrate was treated with 50 mL of ethyl acetate and filtered to obtain a pale yellow solid product, which was 2-phospho-1,4-phthalic acid (BDC-PO3H2).
[0033] (3) Modification of NH2-MIL-53(Fe):
[0034] 5 g of NH2-MIL-53(Fe), 1.25 g of BDC-PO3H2, and 150 mL of DMF were treated at 120 °C for 12 h. After cooling, the solid was separated by centrifugation and dried under vacuum at 80 °C for 12 h to obtain the modified NH2-MIL-53(Fe).
[0035] Example 2
[0036] (1) Preparation of NH2-MIL-53(Fe):
[0037] 5 g of BDC-NH2, 8 g of FeCl3·6H2O, and 80 mL of DMF were placed in a stainless steel high-pressure reactor lined with polytetrafluoroethylene and reacted at 120°C for 6 h. The resulting solid was separated by centrifugation, washed with ethanol, and stirred in fresh ethanol for 24 h to remove residual DMF. After solvent exchange, the product was collected and vacuum dried at 80°C for 16 h to obtain NH2-MIL-53(Fe).
[0038] (2) Preparation of BDC-PO3H2:
[0039] 12 g of 2-iodoterephthalic acid, 60 mL of ice water, and 12.5 mL of concentrated sulfuric acid were mixed thoroughly. Then, 4.65 g of NaNO₂ and 8 g of KI were added, and the mixture was reacted at 120°C for 1.5 h. The product was filtered and recrystallized from toluene to obtain deep yellow crystals, which is dimethyl 2-iodoterephthalate.
[0040] Subsequently, 2 g of dimethyl 2-iodoterephthalate, 10 mL of trimethyl phosphite, and 0.5 g of PdCl2 were reacted at 100 °C for 6 h under N2 protection. The mixture was cooled and filtered, and the filtrate was stirred at 120 °C for 6 h in 6 M HCl (60 mL). The mixture was then concentrated under reduced pressure, and the concentrate was treated with 50 mL of ethyl acetate and filtered to obtain a pale yellow solid product, which was 2-phospho-1,4-phthalic acid (BDC-PO3H2).
[0041] (3) Modification of NH2-MIL-53(Fe):
[0042] 5 g of NH2-MIL-53(Fe), 1.25 g of BDC-PO3H2, and 100 mL of DMF were treated at 140 °C for 10 h. After cooling, the solid was separated by centrifugation and dried under vacuum at 80 °C for 12 h to obtain the modified NH2-MIL-53(Fe).
[0043] Example 3
[0044] (1) Preparation of NH2-MIL-53(Fe):
[0045] 5 g of BDC-NH2, 7.5 g of FeCl3·6H2O, and 60 mL of DMF were placed in a stainless steel high-pressure reactor lined with polytetrafluoroethylene and reacted at 120°C for 6 h. The resulting solid was separated by centrifugation, washed with ethanol, and stirred in fresh ethanol for 24 h to remove residual DMF. After solvent exchange, the product was collected and vacuum dried at 80°C for 16 h to obtain NH2-MIL-53(Fe).
[0046] (2) Preparation of BDC-PO3H2:
[0047] 12 g of 2-iodoterephthalic acid, 50 mL of ice water, and 10.5 mL of concentrated sulfuric acid were mixed thoroughly. Then, 4.65 g of NaNO₂ and 8 g of KI were added, and the mixture was reacted at 120°C for 1.5 h. The product was filtered and recrystallized from toluene to obtain deep yellow crystals, which is dimethyl 2-iodoterephthalate.
[0048] Subsequently, 2 g of dimethyl 2-iodoterephthalate, 12 mL of trimethyl phosphite, and 0.55 g of PdCl2 were reacted at 100 °C for 6 h under N2 protection. The mixture was cooled and filtered, and the filtrate was stirred at 120 °C for 6 h in 80 mL of 6 M HCl. The mixture was then concentrated under reduced pressure, and the concentrate was treated with 50 mL of ethyl acetate and filtered to obtain a pale yellow solid product, which was 2-phospho-1,4-phthalic acid (BDC-PO3H2).
[0049] (3) Modification of NH2-MIL-53(Fe):
[0050] 5 g of NH2-MIL-53(Fe), 1.5 g of BDC-PO3H2, and 100 mL of DMF were treated at 130 °C for 12 h. After cooling, the solid was separated by centrifugation and dried under vacuum at 80 °C for 12 h to obtain the modified NH2-MIL-53(Fe).
[0051] The 1H NMR spectrum (400 MHz, DMSO) of dimethyl 2-iodoterephthalate prepared in Example 1 of this invention is as follows: δ 8.44 (s, 1H), 8.03 (d, J = 9.7 Hz, 1H), 7.81 (d, J = 8.1 Hz, 1H), 3.88 (s, 3H), 3.88 (s, 3H); the 1H NMR spectrum (400 MHz, D2O) of BDC-PO3H2 is as follows: δ 8.50 (d, J = 16.2 Hz, 1H), 8.20 (d, J = 8.0 Hz, 1H), 7.89 (dd, J = 8.1, 4.5 Hz, 1H). Elemental analysis results of NH2-MIL-53(Fe): N (7.44%), C (38.24%), H (3.73%); elemental analysis results of modified NH2-MIL-53(Fe): N (5.75%), C (36.84%), H (4.07%). Based on this, the doping rate of phosphate groups is calculated to be 26.75%.
[0052] X-ray powder diffraction analysis was performed on NH2-MIL-53(Fe) and its modified NH2-MIL-53(Fe), such as... Figure 1 As shown, the diffraction peaks of the prepared NH2-MIL-53(Fe) and its modified NH2-MIL-53(Fe) are consistent with the theoretical simulated diffraction main peak of MIL-53(Fe), indicating that NH2-MIL-53(Fe) and its modified materials were successfully prepared according to Example 1, and the modified NH2-MIL-53(Fe) obtained by ligand exchange did not change the crystal form and structural stability of the original framework.
[0053] Among them, the modified NH2-MIL-53(Fe) of the present invention was tested at 298K and 100% RH and at different times (0~10h), and its proton conductivity hardly decreased, showing long-term cycling stability.
[0054] The modified NH2-MIL-53(Fe) of this invention achieves a maximum proton conductivity of 4.80 × 10⁻⁶ at 343 K and 100% RH. -3 S·cm -1 Compared to NH2-MIL-53(Fe), its conductivity is increased by three orders of magnitude.
[0055] The modified NH2-MIL-53(Fe) of this invention exhibits a proton conductivity of 2.27 × 10⁻⁶ at 55%–100% RH and 298 K. -7 S·cm -1 ~4.80×10 -3 S·cm -1The fact that the proton conductivity increases with increasing relative humidity indicates that under high relative humidity conditions, more adsorbed water molecules act as proton carriers and form richer and denser hydrogen bond channels with BDC-PO3H2, thereby improving the proton transport efficiency.
[0056] This invention modifies NH2-MIL-53(Fe) using BDC-PO3H2, where both BDC-PO3H2 and BDC-NH2 contain terephthalic acid, differing only in the substituents at the ortho-position. Through ligand exchange, BDC-PO3H2 partially replaces BDC-NH2, thus forming a conjugate acid-base pair between the -PO3H2 and -NH2 groups. The -NH3 group of BDC-NH2... + Both the -PO3H2 group and the -PO3H2 group of BDC-PO3H2 can serve as proton sources to provide protons. Furthermore, the -PO3H... - Group, NH3 + Intermolecular hydrogen bonding between the functional group and H2O molecules can construct a denser proton transport channel, thus providing diverse short-distance pathways for proton transfer. After modification with BDC-PO3H2, the modified NH2-MIL-53(Fe) material exhibits increased proton source dissociation ability and shorter distances between proton transition sites compared to NH2-MIL-53(Fe), directly resulting in higher proton conductivity.
[0057] The modified NH2-MIL-53(Fe) of this invention, as a proton conducting material, exhibits excellent proton conduction performance when applied under different temperatures, relative humidity, and time conditions.
[0058] The modified NH2-MIL-53(Fe) of this invention, under conditions of 298–343 K and 100% RH, achieves a proton conductivity of 3.2 × 10⁻⁶. -3 S·cm -1 ~4.8×10 -3 S·cm -1 Within the range, and with increasing temperature, its proton conductivity continuously increases, indicating that high temperature increases the acidity of amino groups, phosphate groups and water molecules, thus promoting proton dissociation.
[0059] Further infrared spectroscopy analysis was performed on the structure of NH2-MIL-53(Fe) and its modified NH2-MIL-53(Fe), such as... Figure 2 As shown, 1583 and 1386 cm -1 The infrared absorption peak at this point is attributed to the asymmetric stretching vibration of the carboxylate, indicating that the carboxylate ligand and Fe... 3+ Coordination occurred at 3462 and 3334 cm. -1This is attributed to the stretching vibration of -NH2, indicating the successful preparation of NH2-MIL-53(Fe). Infrared spectra of the modified NH2-MIL-53(Fe) show values at 1070 and 997 cm⁻¹. -1 The infrared adsorption peak of the phosphate group indicates that BDC-PO3H2 was successfully introduced into the framework of NH2-MIL-53(Fe).
[0060] Application Example 1
[0061] The impedance spectra of the modified NH2-MIL-53(Fe) prepared in Example 1 of this invention in the temperature range of 298~343K at 100% RH are as follows. Figure 3 As shown in the figure. The proton conductivity results indicate that the conductivity of the modified NH₂-MIL-53(Fe) gradually increases with increasing temperature, reaching a maximum of 4.8 × 10⁻⁶ K at 343 K. -3 S·cm -1 This indicates that high temperature promotes the growth of -NH3. + -PO3H - The dissociation from H2O molecules increases the concentration of mobile protons.
[0062] Application Example 2
[0063] The impedance spectra of the modified NH2-MIL-53(Fe) prepared in Example 1 of this invention at 343K and 55%~100% RH are as follows: Figure 4 As shown. Tests on its proton conductivity revealed that, with increasing relative humidity, the conductivity of the modified NH2-MIL-53(Fe) decreased from 2.27 × 10⁻⁶ at 55% RH. -7 S·cm -1 4.8 × 10⁻⁶ when rising to 100% RH -3 S·cm -1 This indicates that under high relative humidity conditions, more adsorbed water molecules act as proton carriers and form richer and denser hydrogen bond channels with BDC-NH2 and BDC-PO3H2 molecules, thereby improving proton transport efficiency.
[0064] Application Example 3
[0065] The impedance spectra of the modified NH2-MIL-53(Fe) prepared in Example 1 of this invention at 298K, 100% RH, and at different times are as follows: Figure 5 As shown in the figure, the proton conductivity of the modified NH2-MIL-53(Fe) hardly decreased after 10 hours of continuous testing, indicating that the modified material has a certain degree of cycle stability.
[0066] Application Example 4
[0067] The activation energy (Ea) of the modified NH2-MIL-53(Fe) prepared in Example 1 of this invention in the temperature range of 298~343K at 100% RH is determined by the Arrhenius equation [σ=σ0exp(-Ea)]. a / k B The value of Ea for the modified NH2-MIL-53(Fe) was calculated using ln(σT) vs 1000 / T. Linear fitting of ln(σT) vs 1000 / T yielded an Ea value of 0.085 eV, as shown in the Arrhenius plot. Figure 6 As shown, the proton conduction of the modified NH2-MIL-53(Fe) follows a transition mechanism. This mechanism can be described as the acidic -NH3 phase of BDC-NH2 in the molecule. + The group and the acidic -PO3H group of BDC-PO3H2 - The phosphonic acid group provides protons, which then undergo transitions in the proton transport channels formed between nitrogen, oxygen, and water molecules. The smaller Ea value also indicates that less energy is required for proton transfer after post-synthetic modification, demonstrating the effectiveness and success of the phosphonic acid group modification strategy.
[0068] In summary, the modified NH2-MIL-53(Fe) material provided by this invention exhibits excellent proton conductivity over a wide operating temperature and humidity range. Furthermore, it maintains a high conductivity value under high relative humidity conditions at room temperature, and its proton conductivity remains almost unchanged after 10 hours of continuous testing. Therefore, it can be widely used as a potential proton conductor in electrochemical devices, sensors, and fuel cells. Simultaneously, the proton conductivity of the modified NH2-MIL-53(Fe) is increased by three orders of magnitude compared to the unmodified form, providing a reference for designing MIL-53 matrix proton conductive materials with ultra-high conductivity.
[0069] Based on the same inventive concept, this invention provides a method for preparing the phosphate-modified NH2-MIL-53(Fe) material as described above, comprising the following steps:
[0070] NH2-MIL-53(Fe) and 2-phospho-1,4-phthalic acid were added to N,N-dimethylformamide and reacted at 120-160℃ for 6-12 h. The reaction product was collected, washed, and dried to obtain the final product.
[0071] In a preferred embodiment, the NH2-MIL-53(Fe) material is prepared by adding FeCl3·6H2O and BDC-NH2 into DMF (N,N-dimethylformamide) and reacting them hydrothermally at a certain temperature.
[0072] In a preferred embodiment, the mass ratio of BDC-NH2 to FeCl3·6H2O in the preparation method of the NH2-MIL-53(Fe) material is 0.5~2; more preferably, the mass ratio of BDC-NH2 to FeCl3·6H2O is 1.2~2.
[0073] In a preferred embodiment, the concentrations of FeCl3·6H2O and BDC-NH2 in DMF during the preparation of the NH2-MIL-53(Fe) material are 0.1~0.25 g / mL; more preferably, the concentrations of FeCl3·6H2O and BDC-NH2 in DMF are 0.15~0.25 g / mL.
[0074] In the preferred embodiment, the reaction temperature in the preparation method of the NH2-MIL-53(Fe) material is 100~160℃, and the holding time is 2~6h.
[0075] The preferred preparation process of BDC-PO3H2 is as follows: 2-iodoterephthalic acid, ice water, concentrated sulfuric acid, NaNO2, and KI are reacted at a certain temperature. The reaction product is recrystallized from toluene to obtain dimethyl 2-iodoterephthalate. Subsequently, dimethyl 2-iodoterephthalate, trimethyl phosphite, and PdCl2 are heated and reacted under N2 protection. The filtrate obtained after the reaction is hydrolyzed in hydrochloric acid and concentrated under reduced pressure to obtain a light yellow solid, which is BDC-PO3H2.
[0076] In a preferred embodiment, the preparation conditions for the above-mentioned dimethyl 2-iodoterephthalate are as follows: the ratio of 2-iodoterephthalic acid, ice water, concentrated sulfuric acid, NaNO2 and KI is 1 (parts by mass): 4~6 (parts by volume): 0.75~1.2 (parts by volume): 0.3~0.45 (parts by mass): 0.6~0.9 (parts by mass); the reaction temperature is 80~120℃; and the reaction time is 1.5~4h.
[0077] The preferred preparation conditions for BDC-PO3H2 are as follows: the ratio of dimethyl 2-iodoterephthalate, trimethyl phosphite, and PdCl2 is 1 (parts by mass): 3-6 (parts by volume): 0.15-0.35 (parts by mass); the reaction temperature is 90-120℃; the reaction time is 2-6 h; the hydrochloric acid concentration is 4-7.5 mol / L; the volume is 40-80 mL; the hydrolysis temperature is 80-110℃; and the hydrolysis time is 8-12 h.
[0078] Based on the same inventive concept, this invention provides an application of the phosphate group-modified NH2-MIL-53(Fe) material as described above in conductive materials.
[0079] In a preferred embodiment, the modified NH2-MIL-53(Fe) material can be used as a proton-conducting material in electrochemical devices.
[0080] In a preferred embodiment, the modified NH2-MIL-53(Fe) material can be used as a proton-conducting material in sensors.
[0081] In a preferred embodiment, the modified NH2-MIL-53(Fe) material can be used as a proton conduction material in fuel cells.
[0082] Example embodiments have been disclosed herein, and while specific terminology has been used, it is for illustrative purposes only and should be construed as such, and is not intended to be limiting. In some instances, it will be apparent to those skilled in the art that features, characteristics, and / or elements described in conjunction with particular embodiments may be used alone, or in combination with features, characteristics, and / or elements described in conjunction with other embodiments, unless otherwise expressly indicated. Therefore, those skilled in the art will understand that various changes in form and detail may be made without departing from the scope of the invention as set forth in the appended claims.
Claims
1. A phosphate-modified NH2-MIL-53(Fe) material, characterized in that, The modified NH2-MIL-53(Fe) material is obtained by exchanging a portion of the ligand 2-amino-1,4-phthalic acid in NH2-MIL-53(Fe) with 2-phospho-1,4-phthalic acid.
2. The phosphate-modified NH2-MIL-53(Fe) material according to claim 1, characterized in that, The NH2-MIL-53(Fe) is formed by the assembly of FeCl3·6H2O and 2-amino-1,4-phthalic acid through coordination.
3. The phosphate-modified NH2-MIL-53(Fe) material according to claim 2, characterized in that, In the NH2-MIL-53(Fe), the mass ratio of 2-amino-1,4-phthalic acid to FeCl3·6H2O is 0.5~2.
4. The phosphate-modified NH2-MIL-53(Fe) material according to claim 1, characterized in that, The 2-phospho-1,4-phthalic acid is prepared from 2-iodoterephthalic acid via iodination, esterification, phosphorous esterification, and hydrolysis.
5. The phosphate-modified NH2-MIL-53(Fe) material according to claim 1, characterized in that, The mass ratio of NH2-MIL-53(Fe) to 2-phospho-1,4-phthalic acid is 1:0.2~0.
3.
6. The phosphate-modified NH2-MIL-53(Fe) material according to claim 1, characterized in that, The phosphate group doping rate in the modified NH2-MIL-53(Fe) material is 20%~35%.
7. The phosphate-modified NH2-MIL-53(Fe) material according to claim 1, characterized in that, The diffraction peaks of the modified NH2-MIL-53(Fe) material in the X-ray powder diffraction pattern are consistent with the main diffraction peaks of the theoretically simulated MIL-53(Fe).
8. The phosphate-modified NH2-MIL-53(Fe) material according to claim 1, characterized in that, The modified NH2-MIL-53(Fe) material shows an infrared spectrum at 1070 cm⁻¹ -1 and 997cm -1 The characteristic absorption peak of the phosphate group is present at the location.
9. A method for preparing a phosphate-modified NH2-MIL-53(Fe) material as described in any one of claims 1 to 8, characterized in that, Includes the following steps: NH2-MIL-53(Fe) and 2-phospho-1,4-phthalic acid were added to N,N-dimethylformamide and reacted at 120-160℃ for 6-12 h. The reaction product was collected, washed, and dried to obtain the final product.
10. The application of the phosphate group-modified NH2-MIL-53(Fe) material as described in any one of claims 1-8 in conductive materials.